Bluetooth-enabled ECG monitoring system - Kho, , T. K; Besar, , Rosli); Tan, , Y. S.; Tee, , K.H.; Ong,, K. C (2006)
Heart disease continues to be the leading cause of mortality in Malaysia in an era of industrialization, changing lifestyles and dietary habits. The mortality rate reported in government hospitals shows an increase in death due to heart diseases, and this trend is expected to continue into the next decades. Since heart disease is increasingly affecting human lifestyle, rehabilitation and practical devices are being carried out and created in order to reduce the disability from heart diseases.